Electrolysis Processes - Vidakovic-Koch, Tanja (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Renewable energies such as solar, hydro or wind power are abundant in principle but subject to strong fluctuations. Therefore, development of new technologies for storage of these renewable energies is of special interest. Electrochemical technologies are ideal candidates for the use of excess current; consequently, an increased electrification of chemical processes is expected. In this respect, there are different pathways to utilize excess current electrochemically. Perhaps the most accepted and discussed solutions involve intermediate energy storage in either chemical energy carriers (such as hydrogen via water electrolysis) or electrochemical energy storage devices (like batteries). Additionally, excess current can put to other uses, such for solutions to environmental issues or for construction purposes, rather than being stored for later use.